Identifying active compounds of soursop ethanolic fraction as α-glucosidase inhibitor - Eko Mugiyanto; Agung Nur Cahyanta; I Made Agus Sunadi Putra; Siswa Setyahadi; Partomuan Simanjuntak (Pharmaciana, 2019)
Postprandial hyperglycemia is triggered by two enteric proteins (α-amylase and α-glucosidase) connected to the brush border of intestinal cells. In diabetic populations, Type 2 Diabetes Mellitus is more prevalent, and α-glucosidase inhibition is the suitable therapy for delaying glucose intake after meals. This study was designed to investigate chemical compounds for their potential inhibitory effects on α-glucosidase. It employed a spectrophotometric method with p-nitrophenyl-α-D-glucopyranose from Saccharomyces cerevisiae as an alpha-glucosidase substrate. The ethanolic fraction was acquired from assay- or activity-guided fractionation. The findings showed that the ethanolic fraction of soursop leaves exhibited the most significant inhibitory activity with an IC50 of 0.17 μg/ml. The data analysis and active compounds identification were carried out by LC-MS and FT-IR. The active compounds of the resulted mixture comprised of Muricatin C, cis-Reticulatacin-10-one, and 3-Methylquercetin 7-[galactosyl-(1->4)-glucoside].